Fragmenting modernism : Ford Madox Ford, the novel, and the Great War - Haslam, Sara (Manchester University Press, 2002)
As a hero of the modernist literary revolution, Madox Ford is a fascinating figure of the time. Haslam explores continuity and crisis in artistic life during the early 20th century through a study of Ford's work and life, highlighting throughout the multi-faceted nature of modernism.